C-Reactive Protein Promotes the Activation of Fibroblast-Like Synoviocytes From Patients With Rheumatoid Arthritis - Fang, Zhengyu; Lv, Jiyang; Wang, Jing; Qin, Qingxia; He, Juan; Wang, Meiying; Zhou, Gengmin; Liu, Guoyu; Zhong, Fubo; Zheng, Yadan; Lan, Hui-Yao; Wang, Qingwen (Frontiers in Immunology, 2020)
Objective: To evaluate the biological effect and mechanisms of C-reactive protein (CRP) on the activation of fibroblast-like synoviocytes (FLSs) from patients with rheumatoid arthritis (RA). Study design: To understand if CRP is involved in RA, expression of CRP and its receptors CD32/64 was examined in synovial tissues from RA patients and normal controls. In vitro, the potential role and mechanisms of CRP in FLS proliferation and invasion, expression of pro-inflammatory cytokines, and activation of its signaling pathways were investigated in both RA-FLS and a normal human fibroblast-like synoviocyte line (HFLS). Results: Compared to normal controls, synovial tissues from 21 RA patients exhibited highly activated CRP signaling, particularly by FLSs as identified by 65% of CRP-expressing cells being CRP+vimentin+ and CD32/64+vimentin+ cells. In vitro, FLSs from RA patients, but not HFLS, showed highly reactive to CRP by largely increasing proliferative and invasive activities and expressing pro-inflammatory cytokines and chemokines, including CCL2, CXCL8, IL-6, and MMP2/9. All these changes were blocked largely by a neutralizing antibody to CD32 and, to a less extent by the anti-CD64 antibody, revealing CD32 as a primary mechanism of CRP signaling during synovial inflammation. Further studies revealed that CRP also induced synovial inflammation differentially via CD32/CD64- NF-kB or p38 pathways as blockade of CRP-CD32-NF-kB signaling inhibited CXCL8, CCL2, IL-6, whereas CRP induced RA-FLS invasiveness through CD32-p38 and MMP9 expression via the CD64-p38-dependent mechanism. Conclusions: CRP signaling is highly activated in synovial FLSs from patients with RA. CRP can induce synovial inflammation via mechanisms associated with activation of CD32/64-p38 and NF-kB signaling.